Realization Of Assertive Speech Acts Performed By The National University Debating Championship Grand Final 2020 - Perdana, Rizky Ramadhan; Bharati, Dwi Anggani Linggar; Yuliasri, Issy (English Education Journal, 2020)
This study was focused on evaluating the realization of the assertive speech acts performed by the government and opposition teams in the NUDC Grand Final 2020. The analysis included the analysis of assertive speech acts, the comparison between the assertive speech act performed by both teams, and the pedagogical implication toward English education. The results of the study showed that twelve types of assertive speech acts were found in their utterances during their speech, such as asserting, arguing, informing, claiming, predicting, suggesting, stating, criticizing, rebutting, reminding, complaining, and reporting assertive speech act in which stating assertive speech act had achieved significant used during the government teams’ speeches. Meanwhile, arguing and criticizing assertive speech act almost reached the highest number of altogether just slightly below stating assertive speech act which confirmed that aside from the declarative statements employed within the arguments, the opposition team was revealed to show their strong disagreement toward the government team’s arguments. Moreover, the realization of the assertive speech act helps English education students to build their communicative skills by considering the purpose and structure of the assertive speech act. For further study, it is expected that future research could examine the combination of assertive speech act and the other speech acts in the debate since the speakers do not merely use assertive speech acts. Since this study also focused on the pedagogical implication for English education, it would be better if future research could scrutinize the implementation of speech acts during the ESL or EFL classroom.